The Immortals : Faces of the Incredible in Buddhist Burma - Rozenberg, Guillaume (Book collections on Project MUSE., 2015)
The cult of the four weikza raises a number of classic anthropological issues, particularly for the anthropology of religion. It also provides a window on contemporary Burmese society. This study makes clear both the indigenous take on reality and the work of anthropological understanding as it is being elaborated, along with the ties that connect the latter to the former.